2009
DOI: 10.1038/ejcn.2008.81
|View full text |Cite
|
Sign up to set email alerts
|

Reduced mania and depression in juvenile bipolar disorder associated with long-chain ω-3 polyunsaturated fatty acid supplementation

Abstract: Long-chain o-3 polyunsaturated fatty acid (LCn-3PUFA) supplementation may improve symptoms of depression in children and bipolar disorder (BD) in adults. No studies have examined the effectiveness of LCn-3PUFA supplementation in the treatment of mania and depression in juvenile BD (JBD) when given as an adjunct to standard pharmacological treatment. Eighteen children and adolescents with JBD received supplements containing 360 mg per day eicosapentaenoic acid (EPA) and 1560 mg per day docosahexaenoic acid (DHA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
84
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(87 citation statements)
references
References 11 publications
3
84
0
Order By: Relevance
“…Intervention length ranged from 6 to 16 weeks. The majority of participants in these studies demonstrated significant declines in depressive and manic symptoms as noted by clinicians on semistructured interviews or other clinical scales (Nemets et al 2006;Wozniak et al 2007;Clayton et al 2009;Gracious et al 2010). Clayton and colleagues (2009) conducted a 6 week open label (i.e., raters and patients were not blinded to study condition) trial of O3 in 18 youth with BD who were also concurrently taking a mood stabilizer.…”
Section: Treatment Of Mood Disordersmentioning
confidence: 86%
See 1 more Smart Citation
“…Intervention length ranged from 6 to 16 weeks. The majority of participants in these studies demonstrated significant declines in depressive and manic symptoms as noted by clinicians on semistructured interviews or other clinical scales (Nemets et al 2006;Wozniak et al 2007;Clayton et al 2009;Gracious et al 2010). Clayton and colleagues (2009) conducted a 6 week open label (i.e., raters and patients were not blinded to study condition) trial of O3 in 18 youth with BD who were also concurrently taking a mood stabilizer.…”
Section: Treatment Of Mood Disordersmentioning
confidence: 86%
“…Clinician ratings of depression and mania decreased ( p = 0.002; p = 0.004), whereas global functioning increased ( p < 0.001). Parent-rated internalizing and externalizing behaviors also decreased ( p = 0.009; p = 0.014) (Clayton et al 2009). Wozniak and colleagues (2007) completed an 8 week open label trial of O3 as monotherapy (with stimulants allowed) for 20 youth with BD.…”
Section: Treatment Of Mood Disordersmentioning
confidence: 91%
“…Nemets et al ( 27 ) observed improved scores in tests for symptoms of depression in depressed children ages 6 to 12 that were given 400 mg of EPA plus 200 mg of DHA daily for 1 month as compared with children who received placebo. Clayton et al ( 26 ) provided 360 mg of EPA plus 1,560 mg of DHA as an adjunct to pharmacotherapy in 18 female bipolar depressed teens (average 16 years old) that had been stabilized for 6 weeks on lithium and valproate. Compared with within-individual baseline data, the supplementation caused a substantial elevation of RBC DHA and EPA content, and a signifi cant decrease in clinical scores of depression.…”
Section: Downloaded Frommentioning
confidence: 99%
“…Indeed, DHA defi ciency throughout development leads to decreased DHA levels in neural tissue and is associated with defi cits in psychomotor development ( 21 ), problem solving ( 22 ), reading skills ( 23 ), visual acuity ( 24 ), and attention ( 25 ). Furthermore, emerging clinical data support a link between suffi cient DHA intake with a reduction in the incidence and/or symptomatic relief of adolescent depression ( 5,(26)(27)(28)(29), and there exists an abundance of clinical evidence supporting a positive role for the omega-3 PUFA EPA in the treatment of adult depression ( 30 ). However, the studies examining the importance of DHA, in particular, are limited in scope and interpretation, and no longitudinal studies have been reported to date.…”
mentioning
confidence: 99%
“…Clayton reported that in pediatric bipolar disorder, DHA concentrations were associated with depression severity; while EPA concentrations were more closely associated with manic symptoms. 70 These results were replicated in a study of adults with bipolar disorder that reported omega-3 fatty acid concentrations and omega-6:omega-3 ratio were associated with severity of manic symptoms. 71 Three open-label trials have found adjunctive omega-3 fatty acid supplementation to be effective in bipolar disorder (Table 3).…”
Section: Bipolar Disordermentioning
confidence: 76%